2016
DOI: 10.1002/jcu.22383
|View full text |Cite
|
Sign up to set email alerts
|

Patent foramen ovale diagnosis: The importance of provocative maneuvers

Abstract: Patent foramen ovale (PFO) is a frequent congenital anomaly, but massive right-to-left shunt (RTLS) is normally prevented by higher pressures in left heart chambers. However, mechanical ventilation with positive end-expiratory pressure (PEEP) can significantly increase right atrial pressure, accentuating the RTLS, mainly after major cardiothoracic surgery. We report a patient admitted to the intensive care unit after cardiac surgery. Pre- and intraoperative transesophageal echocardiography only described an an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
0
5
0
3
Order By: Relevance
“…Various maneuvers increase the sensitivity of screening tests for intracardiac shunt [28]. If no shunt was detected after the first injection, it was repeated on release of a Valsalva maneuver (spontaneously breathing patients), or on release of an inspiratory hold (mechanically ventilated patients).…”
Section: Assessment Of Shunt Using Intravenous Saline Microbubble Conmentioning
confidence: 99%
“…Various maneuvers increase the sensitivity of screening tests for intracardiac shunt [28]. If no shunt was detected after the first injection, it was repeated on release of a Valsalva maneuver (spontaneously breathing patients), or on release of an inspiratory hold (mechanically ventilated patients).…”
Section: Assessment Of Shunt Using Intravenous Saline Microbubble Conmentioning
confidence: 99%
“…5) In this patient, we did not perform clinical autopsy. In addition, we did not perform transesophageal echocardiography during Valsalva maneuver, which is reportedly useful for the detection of patent foramen ovale, 6) or lower extremity ultrasonography after thrombectomy due to exacerbation of the general condition. Therefore, deep venous thrombosis Fibrin-dominant thrombi with few red blood cell components have been reported to be hard, 9,10) but soft parts of the thrombus may have been fragmented by the two procedures using Trevo provue, and only the fibrin-rich part of the thrombus may have remained.…”
Section: Discussionmentioning
confidence: 99%
“…Maneuvers have been investigated not just by echocardiography, but also with direct pressure measurement in the catheterization laboratory. In a hemodynamic study from 2001, investigators compared Valsalva maneuver to coughing, deep inspiration, and three different expiration pressures (20,40, and 60 mm Hg) with simultaneous RAP and pulmonary capillary wedge pressure (PCWP) measurements in the laboratory. 11 With a sample size of 50 consecutive patients, they concluded that the Valsalva was the most effective maneuver to maximize right-to-left inter-atrial pressure gradient, closely followed by high expiration pressure (60 mm Hg), deep inspiration, and coughing.…”
Section: Introductionmentioning
confidence: 99%
“…18 Second harmonic imaging has been shown to enhance PFO detection during TTE. 19 Other clinical scenarios, such as mechanical ventilation with positive end-expiratory pressure (PEEP) 20 or high plateau pressure, 21 can raise right atrial pressure and accentuate shunt detection. High tidal volumes or high PEEP may raise transpulmonary pressure, compressing pulmonary arterial vasculature and thereby raising pulmonary vascular resistance and right ventricular afterload, which in turn may raise RAP and uncover a PFO.…”
Section: Introductionmentioning
confidence: 99%